2019
DOI: 10.1016/j.catcom.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Reversible deactivation of γ-alumina by steam in the gas-phase dehydration of methanol to dimethyl ether

Abstract: Reversible deactivation of γ-alumina by steam in the gas-phase dehydration of methanol to dimethyl ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The experimental procedure for the γ-alumina catalyst testing can be found in previous work. 27 A combination of commercially obtained CZA catalyst, γ-Al 2 O 3 catalyst and zeolite 3A adsorbent were used for the experimental demonstration of direct DME synthesis from CO/CO 2 /H 2 -mixtures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental procedure for the γ-alumina catalyst testing can be found in previous work. 27 A combination of commercially obtained CZA catalyst, γ-Al 2 O 3 catalyst and zeolite 3A adsorbent were used for the experimental demonstration of direct DME synthesis from CO/CO 2 /H 2 -mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Reaction kinetics have been determined for the used catalyst materials by fitting the parameters in the models of Graaf et al (1988) and Berčič et al (1992) for the methanol synthesis and methanol dehydration respectively, shown in Table 2. 5,27,30,31 The steam adsorption isotherm of the LTA zeolite adsorbent is determined under the high pressure and temperature working conditions of the SEDMES process. A Sips isotherm best describes the experimental data, in accordance with the available literature at lower temperature and pressure conditions.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, the production and efficient handling of steam remains a major bottleneck for industrial CO 2 utilization (Centi and Perathoner 2009; Accelerating Breakthrough Innovation in Carbon Capture 2017; Katelhon et al 2019). In this context, several groups have experimentally demonstrated the benefit of sorption enhancement in terms of product yield that exceeds the thermodynamic equilibrium in absence of steam adsorption (van Kampen et al ,2020aKim et al 2001;Carvill et al 1996;Borgschulte et al 2013;Ressler et al 2006;Choi et al 2002;Boon et al 2019;Liuzzi et al 2020). In parallel, modelling studies on sorption enhanced reactions have sought to conceptually understand sorption enhancement and focus on process design (van Kampen et al 2020b;Iliuta et al 2011;Parra et al 2017Parra et al ,2018Bayat et al 2016;Guffanti et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Sorption enhanced DME synthesis (SEDMES), which combines direct DME synthesis with in situ water removal using a solid adsorbent, is a promising process intensification for the direct production of DME from CO 2 . 7,[11][12][13] While enabling increased single-pass conversion and selectivity, experimental studies have indicated that time and energy intensive temperature swing regeneration would be required for adsorbent regeneration. 7,13 A potentially faster and more energy efficient approach is pressure swing regeneration as recently indicated in a SEDMES modelling study.…”
mentioning
confidence: 99%